SELF-CONFIDENCE AND SATISFACTION AMONG NURSING STUDENTS WITH THE USE OF HIGH FIDELITY SIMULATION AT ARAB AMERICAN UNIVERSITY, PALESTINE - Salameh, Basma Saleem (LIFE: International Journal of Health and Life-Sciences, 2017)
High fidelity simulation practice has now become an important part of the education of nursing students to enhance their clinical skill confidence and satisfaction. To achieve our aim of providing the community with highly skilled nurses, the current study set out to assess the level of self-confidence and satisfaction among nursing students with the use of High Fidelity Simulation at Arab American University of Jenin (AAUJ). The research design was a quantitative, cross-sectional descriptive study, with a total of 440 nursing students who were in year 2, year 3 and year 4 of the BSc program at the Arab American University of Jenin. The AAUJ is the first university to introduce HFS among Palestinian universities. Data was collected using: (a) demographic survey, (b) “Self-Confidence and Satisfaction among nursing students Questionnaire”, created by NLN which consists of 13 items with five points on the Likert scale. Majority of the participants were female (53.6%), ages 21-22(58.6%). Most (50.5%) of the participants were in the second year of study, 48.9% of the total participants were engaged in the adult health nursing specialty course and the majority (58.0) had GPAs between 1.75 and 2.75. This study found that most nursing students were satisfied (80.7%) and self-confident (75.4%) with the simulation-based learning in nursing education. Moreover, we found no statistically significant differences between age, gender, and the total mean score from the questionnaire. However, specialty course and year level returned some difference among the groups (P<0.000). The study’s findings also revealed that high-fidelity simulation improves nursing students’ self-confidence and satisfaction. Given the shortage of clinical settings, simulation can bridge the gap as an effective teaching tool and an innovative pedagogical strategy in Palestine. Future studies might focus on maternity nursing students’ perceptions and experiences regarding high-fidelity simulation due to the restrictions applied to male students’participationin maternity courses.